Transport of statins by multidrug resistance-associated proteins 1 and 5 - Tuomi, Suvi-Kukka (My University, 2025)
Statins are widely used in the treatment of hypercholesterolemia but also associated with muscle-related adverse effects. Multidrug resistance-associated protein (MRP) 1 and 5 are expressed in the skeletal muscle, where they may regulate intramuscular levels of their substrates. Here, we investigated the transport of various statins by MRP1 and MRP5 with the vesicular transport assay. Statin concentrations in the vesicles were determined with liquid chromatography tandem mass spectrometry. At 6 μm statin concentration, MRP1 transported both 3R,5S-fluvastatin and 3S,5R-fluvastatin with uptake ratios of 2.6 and 2.0. MRP5 transported 3R,5S-fluvastatin, 3S,5R-fluvastatin, and 10 μm pitavastatin with uptake ratios of 2.9, 3.7, and 2.6, respectively. Atorvastatin was only a weak substrate of MRP5 with an uptake ratio of 1.6 and was therefore not investigated further. In concentration-dependent transport experiments, racemic fluvastatin was transported by MRP1 and MRP5 with apparent affinities (Km) of 225 μm and 23 μm. Pitavastatin was transported by MRP5 with a Km value of 433 μm. In vitro clearance (CLin vitro) of fluvastatin was 0.36 μl/min/mg for MRP1, while MRP5 exhibited a CLin vitro value of 1.2 μl/min/mg for fluvastatin and 0.21 μl/min/mg for pitavastatin. Pravastatin, rosuvastatin, and simvastatin acid were not transported by MRP1 or MRP5. Atorvastatin and pitavastatin were not transported by MRP1. These data indicate that MRP1 transports fluvastatin, while MRP5 transports both fluvastatin and pitavastatin. Because MRP1 and MRP5 are expressed in the skeletal muscle, they may reduce myocyte exposure to fluvastatin and pitavastatin and protect from muscle toxicity.
Keywords: skeletal muscle toxicity, MRP1, MRP5, statin-related myotoxicity, fluvastatin, pitavastatin